Analisis Tingkat Risiko Kredit dengan Menggunakan Credit Risk Ratio, Analisis Trend dan Common Size pada PT Bank Tabungan Negara (Persero), Tbk. Cabang Samarinda - Yulius Gessong Sampeallo; Angela Avenia (Politeknik Negeri Samarinda, 2022)
The research objective is to determine the level of credit risk in terms of Non Performing Loans (NPL) at PT. Bank Tabungan Negara (Persero), Tbk Branch Samarinda by using credit risk ratio, trend analysis and common size. This research analysis tool includes Credit Risk Ratio, Trend Analysis and Common Size. The results of the Credit Risk Ratio analysis show that seen from the average percentage level of risk PT. The Samarinda State Savings Bank (Persero), Tbk Branch, which is determined by Bank Indonesia, which is 5%, is still below the percentage for high risk categories, which is 4.21%. And for Trend Analysis shows that credit collectibility experiences fluctuations every year. While Common Size also shows that credit collectability has fluctuations in total credit collectibility.